발목 인공관절 치환술 후 심부정맥혈전증으로 오인된 스파르가눔증: 증례 보고 - 조재호; Otgonsaikhan Nomkhondorj; Jaeho Cho (대한족부족관절학회지, 2025)
Sparganosis is a rare parasitic infection caused by the plerocercoid larvae of the Spirometra species. It can present as nonspecific calf pain and swelling, often mimicking deep vein thrombosis (DVT), especially in postoperative patients. This paper reports a case of a 78-year-old male with a history of total ankle arthroplasty who presented with recurrent calf pain and swelling. The initial clinical evaluation raised suspicion for DVT, and Doppler ultrasound was performed. Imaging revealed a hypoechoic, serpiginous structure suggestive of a parasitic infection. Surgical exploration confirmed sparganosis through the removal of the larvae. The patient's symptoms resolved completely after the procedure. This case highlights the need to consider sparganosis in the differential diagnosis of unexplained calf symptoms, particularly in patients with potential exposure to endemic areas or sources of a parasitic infection, regardless of the coexisting surgical history.